2019
DOI: 10.11613/bm.2019.030710
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing moving average control procedures for small-volume laboratories

Abstract: Introduction: Moving average (MA) means calculating the average value from a set of patient results and further using that value for analytical quality control purposes. The aim of this study was to examine whether the selection, optimization and validation of MA procedures can be performed using the already described bias detection simulation method and whether it is possible to select appropriate MA procedures for a laboratory with a small daily testing volume. Materials and methods: The study was done on fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…The MR program with simulated optimal parameters could consistently detect positive of 0.06 ng/ml and above, or negative of 0.4 ng/ml and above biases, at an average daily run size of 10. A comparison of the two PBRTQC programs revealed that the MA program rejected as many outliers as possible to narrow the CL and to improve the detection sensitivity, but the increased rejection rate of the data reduced the frequency of calculating patient results, leading to possible delays in rejection and the possibility of not detecting particularly large biases 19,20 . After converting the results into the binary state, the MR program had no TLs and excessive concentrations for judgment, but had higher data utilization than the MA program, so it is very suitable for analyses with small volumes of data such as that in this study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The MR program with simulated optimal parameters could consistently detect positive of 0.06 ng/ml and above, or negative of 0.4 ng/ml and above biases, at an average daily run size of 10. A comparison of the two PBRTQC programs revealed that the MA program rejected as many outliers as possible to narrow the CL and to improve the detection sensitivity, but the increased rejection rate of the data reduced the frequency of calculating patient results, leading to possible delays in rejection and the possibility of not detecting particularly large biases 19,20 . After converting the results into the binary state, the MR program had no TLs and excessive concentrations for judgment, but had higher data utilization than the MA program, so it is very suitable for analyses with small volumes of data such as that in this study.…”
Section: Discussionmentioning
confidence: 95%
“…A comparison of the two PBRTQC programs revealed that the MA program rejected as many outliers as possible to narrow the CL and to improve the detection sensitivity, but the increased rejection rate of the data reduced the frequency of calculating patient results, leading to possible delays in rejection and the possibility of not detecting particularly large biases. 19 , 20 After converting the results into the binary state, the MR program had no TLs and excessive concentrations for judgment, but had higher data utilization than the MA program, so it is very suitable for analyses with small volumes of data such as that in this study. Furthermore, the PCT results of the population showed a skewed distribution, leading to a reduction in the applicability of the MA method.…”
Section: Discussionmentioning
confidence: 99%
“…Selection of the optimal MA procedure for each of the 10 examined clinical chemistry analytes was previously done using the bias detection simulation method described by van Rossum ( 7 , 12 , 13 ). The bias detection simulation method comprises the examination of different combinations of MA procedure parameters for each analyte and the ability of each examined MA procedure to detect biases of different sizes through dedicated software.…”
Section: Methodsmentioning
confidence: 99%
“…The bias detection simulation method comprises the examination of different combinations of MA procedure parameters for each analyte and the ability of each examined MA procedure to detect biases of different sizes through dedicated software. We have previously described in detail the process of selecting, optimizing, and validating MA procedures on the example of creatinine, potassium, sodium, and albumin ( 12 ). Respectively, the same was done for the other six analytes.…”
Section: Methodsmentioning
confidence: 99%
“…A major breakthrough is that one of these methods has been made available online in the MA Generator application, so that laboratories can readily use the advanced simulation techniques to set up and validate their laboratory-specific PBRTQC procedures. 20,21 Using these new optimization techniques to design PBRTQC procedures in routine practice, it has been shown that PBRTQC application is feasible and valuable for (rapid) detection of relevant errors and increases the effectiveness and cost-effectiveness of quality control plans. 3,16,18,19 Insights and guidance on when to select which type of calculation algorithm for PBRTQC are needed to enhance further the performance and application of PBRTQC.…”
Section: Patient-based Real-time Quality Controlmentioning
confidence: 99%